A Decision Support System for Regional Sustainable Development: The Flag Model - Peter Nijkamp; Hans Ouwersloot (Tinbergen Institute, 1997)
This paper presents a new approach to the analysis of spatial sustainability, with a particular view on agriculture. After a methodological introduction, a new tool - the so-called Flag model - is introduced in order to assess the degree of sustainability of various policy alternatives. The model is tested by means of a case study for the island of Lesvos, Greece.
Keywords: 330; Nachhaltige Entwicklung; Management-Informationssystem; Regionalökonomik; Theorie